Evidence-informed recommendations to reduce dissemination bias in clinical research: conclusions from the OPEN (Overcome failure to Publish nEgative fiNdings) project based on an international consensus meeting. Issue 5 (5th May 2015) - Meerpohl, Joerg J; Schell, Lisa K; Bassler, Dirk; Gallus, Silvano; Kleijnen, Jos; Kulig, Michael; La Vecchia, Carlo; Marušić, Ana; Ravaud, Philippe; Reis, Andreas; Schmucker, Christine; Strech, Daniel; et al.
Abstract : Background: Dissemination bias in clinical research severely impedes informed decision-making not only for healthcare professionals and patients, but also for funders, research ethics committees, regulatory bodies and other stakeholder groups that make health-related decisions. Decisions based on incomplete and biased evidence cannot only harm people, but may also have huge financial implications by wasting resources on ineffective or harmful diagnostic and therapeutic measures, and unnecessary research. Owing to involvement of multiple stakeholders, it remains easy for any single group to assign responsibility for resolving the problem to others. Objective: To develop evidence-informed general and targeted recommendations addressing the various stakeholders involved in knowledge generation and dissemination to help overcome the problem of dissemination bias on the basis of previously collated evidence. Methods: Based on findings from systematic reviews, document analyses and surveys, we developed general and targeted draft recommendations. During a 2-day workshop in summer 2013, these draft recommendations were discussed with external experts and key stakeholders, and refined following a rigorous and transparent methodological approach. Results: Four general, overarching recommendations applicable to all or most stakeholder groups were formulated, addressing (1) awareness raising, (2) implementation of targeted recommendations, (3) trial registration and results posting, and (4) systematic approaches to evidence synthesis. These general recommendations are complemented and specified by 47 targeted recommendations tailored towards funding agencies, pharmaceutical and device companies, research institutions, researchers (systematic reviewers and trialists), research ethics committees, trial registries, journal editors and publishers, regulatory agencies, benefit (health technology) assessment institutions and legislators. Conclusions: Despite various recent examples of dissemination bias and several initiatives to reduce it, the problem of dissemination bias has not been resolved. Tailored recommendations based on a comprehensive approach will hopefully help increase transparency in biomedical research by overcoming the failure to disseminate negative findings.